Tamara Gundorova, Tranzytna kultura. Symptomy postkolonialnoji travmy, Vyd. Grani-T, Kyjiv 2013, ss. 548. - Kupidura, Ryszard (Porównania, 2014)
Tamara Gundorova, Tranzytna kultura. Symptomy postkolonialnoji travmy, Vyd. Grani-T, Kyjiv 2013, ss. 548